Patient safety and quality of care in mental health: a world of its own?. (October 2017) - D'Lima, Danielle; Crawford, Mike J.; Darzi, Ara; Archer, Stephanie
Summary: Quality and safety in healthcare, as an academic discipline, has made significant progress over recent decades, and there is now an active and established community of researchers and practitioners. However, work has predominantly focused on physical health, despite broader controversy regarding the attention paid to, and significance attributed to, mental health. Work from both communities is required in order to ensure that quality and safety is actively embedded within mental health research and practice and that the academic discipline of quality and safety accurately represents the scientific knowledge that has been accumulated within the mental health community.